A Flea-Borne Mystery: Unraveling Murine Typhus in a Patient with Unexplained Encephalopathy - Jose Loayza Pintado MD; Jorge Aboytes MD; Cesar Uribe MD (Journal of Investigative Medicine High Impact Case Reports)
Murine typhus is a flea-borne rickettsial infection caused by Rickettsia typhi , commonly seen in endemic regions like Southern California and Texas. While it typically presents with fever, rash, and headache, neurological symptoms such as altered mental status are rare. We present a case of a 66-year-old male in southern Texas with alcohol use disorder who developed progressive confusion, decreased appetite, and subjective fevers. He was found to have severe hyponatremia, acute kidney injury, and atrial fibrillation with rapid ventricular response. Despite supportive care and empiric antibiotics for a urinary tract infection, his encephalopathy persisted. Further history revealed exposure to flea-infested cats, prompting rickettsial testing and empiric doxycycline. Typhus immunoglobulin M antibodies later confirmed the diagnosis, and the patient showed marked improvement with doxycycline therapy. Murine typhus with altered mental status is a rare presentation, often leading to diagnostic delays. This case occurred in an endemic region, with exposure to flea-infested cats as a significant risk factor. The patient’s persistent encephalopathy prompted a broad workup, including rickettsial testing, which was confirmed on serology testing. Early doxycycline initiation led to symptom resolution. This case highlights a rare neurological presentation of murine typhus and emphasizes the importance of considering it in patients with unexplained encephalopathy in endemic areas.